Impact of triangular irregularity, material heterogeneity and initial stress on the propagation of shear waves in a transversely isotropic porous layer - Kumar, Ravinder; Sharma, Suraj; Chandel, Sourav (Zielona Góra: Uniwersytet Zielonogórski)
In this work, the behaviour of shear waves in a FSPL that is initially stressed exhibits transverse isotropy is investigated. The layer is located on an elastic half-space, characterized by a triangular shaped irregularity at interface of contact. This research derives the dispersion equation of shear waves utilizing elasticity theory by Biot, combined with perturbation techniques and Fourier transformations.
Keywords: triangular irregularity; material heterogeneity; shear waves; initial stress; porous media